2011
DOI: 10.1292/jvms.10-0485
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Morphological Studies of Double-Chambered Right Ventricle in Dogs

Abstract: The double-chambered right ventricle (DCRV) is a rare congenital cardiac disease in dogs, and its detailed epidemiological and morphological features are not clearly understood. By investigating the profile, clinical signs, and characteristics of examination findings of eleven dogs with DCRV by means of a retrospective study, we attempted to clarify the epidemiology and morphology of the condition. The study group consisted of nine males and two females. Breeds included Pug (n=3), Miniature Dachshund (n=1), Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…388,390,396,[398][399][400][401][402][403] Abnormalities observed by 2D imaging include valvular thickening (dysplasia), fusion along the commissural edges, and varying degrees of annular hypoplasia. There is some controversy among cardiologists about the criteria for the diagnosis of subvalvular or infundibular pulmonary stenosis 400 versus double chambered right ventricle, 371,[404][405][406][407][408][409] especially in cats (Figure 8-49, C; . There is some controversy among cardiologists about the criteria for the diagnosis of subvalvular or infundibular pulmonary stenosis 400 versus double chambered right ventricle, 371,[404][405][406][407][408][409] especially in cats (Figure 8-49, C; .…”
Section: Pulmonic Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…388,390,396,[398][399][400][401][402][403] Abnormalities observed by 2D imaging include valvular thickening (dysplasia), fusion along the commissural edges, and varying degrees of annular hypoplasia. There is some controversy among cardiologists about the criteria for the diagnosis of subvalvular or infundibular pulmonary stenosis 400 versus double chambered right ventricle, 371,[404][405][406][407][408][409] especially in cats (Figure 8-49, C; . There is some controversy among cardiologists about the criteria for the diagnosis of subvalvular or infundibular pulmonary stenosis 400 versus double chambered right ventricle, 371,[404][405][406][407][408][409] especially in cats (Figure 8-49, C; .…”
Section: Pulmonic Stenosismentioning
confidence: 99%
“…This is an ostium primum ASD. 371,[404][405][406][407][408][409]520 Doppler imaging both verifies the shunt and helps to assess the severity of the lesion. The valve is incompetent (right panel) and in real time studies the regurgitant jet started in the LV and crossed the ASD to enter both atria.…”
Section: Overview and Practical Considerationsmentioning
confidence: 99%
“…In this malformation, the right ventricular cavity is divided into two parts by an abnormal muscular, fibromuscular, or fibrous band, sometimes with thick endocardial proliferation on its rim. The right ventricular cavity thus becomes divided into a proximal "high-pressure" chamber and distal "lowpressure" chamber [41,42]. The location of this band may vary but is usually downstream of the tricuspid septal leaflet, connecting the ventricular septum to the anterior wall of the right ventricle ( Figure 19-13) [43].…”
Section: Subvalvular Pulmonic Stenosismentioning
confidence: 99%
“…This condition has been described in dogs, human beings [ 3 5 ], cats [ 6 ], and alpacas [ 7 ]. The dog breeds most frequently affected by this anomaly are large, such as Golden Retriever [ 2 , 8 ] and Boxer [ 9 ]. A case of DCRV was also reported in a Pug [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A case of DCRV was also reported in a Pug [ 10 ]. One study reported no sex predisposition [ 10 ] and another suggested that males were overrepresented [ 8 ]. There are two types of DCRV reported in human beings: a low (oblique) type [ 11 ] and a high (horizontal) type [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%